(untitled) (Research, Society and Development, 2021)
Introduction: Lung cancer is the most common malignant neoplasm in Brazil, adenocarcinoma being the most prevalent type, strongly associated with smoking. Some common symptoms are: persistent cough, hemoptysis, angina, shortness of breath, hoarseness and weight loss. Screening and early diagnosis are important measures for better prognosis, but it presents a challenge due to limited access to imaging tests. Objective: To describe the epidemiological understanding of lung cancer diagnosis in Brazil in association with its main modifiable risk factor, smoking. Methodology: Descriptive, retrospective epidemiological study with a quantitative approach. Data collection from the Department of Informatics of the Unified Health System (DATASUS), in the following databases: TABNET and INCA. Results and discussion: Between 2013 and 2020, there were a total of 2440428 cases of lung cancer in Brazil, with about 55% of cases affecting women in this period. Regarding the age group, the most affected is over 40 years, predominantly females in the age group 40 to 59 years and males in the age group 60 years or more. According to the federation units, the incidence of lung cancer in Brazil is led by the state of São Paulo, followed by Minas Gerais and Rio Grande do Sul. Conclusion: Lung cancer is the most frequent neoplasm in Brazil, affecting mostly women over 40 years of age, associated with lifestyle habits and exposure to risk factors such as smoking.